Perspectives on contemporary literature. - Hershberg, David (The University Press of Kentucky, 2015)
In all parts of the world and in every age, many of the greatest works of literature have been shaped or inspired by the swirl of historical events. The wars, holocausts, and mushroom clouds of our own era haunt the pages of many twentieth-century writers; events of the past, even the remote past, also inspire many authors, though their work is contemporary in every way. And if we agree with the poet Czeslaw Milosz that ""historicity may reveal itself in a detail of architecture, in the shaping of a landscape, "" we come to recognize that our understanding of a given poem or novel can often be